Recovering liberties Indian thought in the age of liberalism and empire : the Wiles lectures given at the Queen's University of Belfast, 2007 - Bayly, Christopher Alan 1945-2015 (Cambridge University Press, 2012)
One of the world's leading historians examines the great Indian liberal tradition, stretching from Rammohan Roy in the 1820s, through Dadabhai Naoroji in the 1880s to G. K. Gokhale in the 1900s. This powerful new study shows how the ideas of constitutional, and later 'communitarian' liberals influenced, but were also rejected by their opponents and successors, including Nehru, Gandhi, Indian socialists, radical democrats and proponents of Hindu nationalism. Equally, Recovering Liberties contributes to the rapidly developing field of global intellectual history, demonstrating that the ideas we associate with major Western thinkers – Mills, Comte, Spencer and Marx – were received and transformed by Indian intellectuals in the light of their own traditions to demand justice, racial equality and political representation. In doing so, Christopher Bayly throws fresh light on the nature and limitations of European political thought and re-examines the origins of Indian democracy
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 1858-1910; Geschichte 1820-1910; Geschichte; Liberalism / India / History; Democracy / India; Liberalismus; Indien; Britisch-Indien